Blue Covenant: Strategies for managing Water Stress in Dwarka, New Delhi, India (Global Journals of Research in Engineering, 2022)
Water is an indispensable resource available on earth for all living beings. A decline in the quality and quantity of water is now a global issue of concern. Due to the increasing demand controversy can be seen over command and sharing over water. Hence water stress is a complex issue which deserves urgent global attention and actions. Water stress refers to the ability, or lack thereof, to meet human and ecological demand for water. Therefore, this research aims to understand the reasons for water stress through different summits, policies and case studies. The main focus of this research is to frame strategies for waster stress management in Dwarka, Delhi, India. It is also known for being the largest sub-city in Asia with a potential for further development. Dwarka is already facing water stress and further development will only add to the tension on water supply and its availability in future. In-depth research is done on the existing water infrastructure and the potential to reduce water stress in Dwarka. Based on these studies strategies and proposals were formed to effectively reduce water stress in Dwarka. This study will help in planning for an area concerning the available resources. The outcome of this study is to practice different short and long term goals which can be followed to reduce the intensity of water stress and less dependency on the available resources.